Cover - Gonçalves, Sergio Eduardo de Paiva; carara, Jacqueline (Brazilian Dental Science, 2017)
Figure of the article: Radiographic and scanning electron microscopic assessment of root canal filling remnants after endodontic re-instrumentation Authors: Luciane Geanini Pena Santos, Wilson Tadeu Felippe, Beatriz Dulcineia Mendes Souza, Andrea Cristina Konrath, Mabel Mariela Rodríguez Cordeiro, Mara Cristina Santos Felippe